Effects of chin advancement surgery in hyoid bone and tongue positions and in the dimension of the oropharynx - Milena Barreto de Arruda Cabral; André Carlos de Freitas; Telma Martins de Araújo; Nilson Pena; Rivail Almeida Brandão Filho (Dental Press Editora, 2013)
INTRODUCTION: Advancement genioplasty has been increasingly indicated for the correction of anterior mandibular deficiency as it balances the patient's profile and generates functional changes. OBJECTIVE: Thus, the aim of this study was to assess the effects of advancement genioplasty in the oropharyngeal size and in the position of the hyoid bone and tongue. METHODS: The sample comprised 22 lateral cephalometric radiographs of 11 individuals who had undergone advancement genioplasty alone. Eleven of these radiographs depicted the immediate preoperative period (T0) and the other 11 the postoperative period after at least four months (T1). The radiographs were scanned and exported to the Radiocef Studio 2.0® software (Radio Memory Ltda., Belo Horizonte, MG, Brazil). The landmarks were then identified and automatically measured by the program. RESULTS: The results showed statistically significant differences between the horizontal position of the hyoid bone and tongue and in the oropharyngeal size. The hyoid bone and tongue were repositioned anteriorly after surgery (p = 0.01), thereby increasing the dimension of the oropharyngeal airspace (p = 0.01). CONCLUSIONS: The oropharyngeal dimension increased as the tongue base and hyoid bone were repositioned more anteriorly